2022
DOI: 10.12688/gatesopenres.13588.2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health and rights knowledge, perceptions, and experiences of adolescent learners from three South African townships: qualitative findings from the Girls Achieve Power (GAP Year) Trial

Abstract: Background: Adolescence is a time of psycho-social and physiological changes, with increased associated health risks including vulnerability to pregnancy, HIV, sexually transmitted infections, and gender-based violence. Adolescent learners, from three townships in South Africa, participated in a 44 session, after-school asset-building intervention (GAP Year), over 2 years providing sexual and reproductive health (SRH) education. This paper explores adolescent learners’ SRH, sexual risk and rights knowledge; pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Cultural, religious, and traditional norms played a significant role in hindering open discussions about sex and sexual matters [28]. The lack of trust in healthcare providers (HCPs) also limited access to SRH services among adolescents and young people.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural, religious, and traditional norms played a significant role in hindering open discussions about sex and sexual matters [28]. The lack of trust in healthcare providers (HCPs) also limited access to SRH services among adolescents and young people.…”
Section: Discussionmentioning
confidence: 99%
“…In their research in Cape Town, Krogstad et al ( 45 ) found that the uptake of contraceptive implants was declining, due in part to real experiences or myths about women being assaulted by robbers who physically remove the implants to smoke as drugs. In another study in the Western Cape and Gauteng, adolescent girls also mentioned this myth during focus group discussions ( 46 ). This reinforces the need for accurate information sharing and demand creation, especially about the composition of the implant.…”
Section: Discussionmentioning
confidence: 96%
“…Adolescents' limited access to information about reproductive health and the dangers of sex before marriage are also obstacles. Efforts must be made to limit barriers to accessing health services and facilitate more adolescent-friendly reproductive health information and services, including reconsidering health training strategies [29].…”
Section: Discussionmentioning
confidence: 99%